Daily but not pulse calcitriol therapy improves growth in experimental uremia - Mehls, Otto; Knöller, Nora; Oh, Jun; Wesch, Horst; Wünsche, B.; Schmitt, Claus P. (Pediatric nephrology, 2000)
Calcitriol (C) pulse therapy is widely used to suppress secondary renal hyperparathyroidism. However, high C serum concentrations may have an antiproliferative effect on growth cartilage cells and may suppress growth rate. The study was designed to evaluate whether daily C and pulse C therapy have differential effects on growth in uremic rats. Female Sprague-Dawley rats (150 g, n=5-10 per group) underwent two-stage subtotal nephrectomy (U). The duration of uremia was 14-18 days. The animals were fed a standard diet or a diet with a low-calcium content. Rats on a low-calcium diet were randomized for recombinant human growth hormone (rhGH) treatment (2.5 IU/kg per day) or solvent. C was injected subcutaneous twice daily (15 pmol/day) or intraperitoneal (105 pmol) twice per week. Weight gain and length gain was determined weekly. After sacrifice, total body calcium was determined by total body neutron activation analysis. Bone micromorphometric analysis of third lumbar vertebra and double staining with tetracycline for determination of mineralization rate were performed. Whereas daily C significantly increased total body length gain within 2 weeks, pulse C did not (U solvent 4.0±0.3 cm, UC bolus 4.3±0.4 cm, UC daily 5.3±0.3 cm, P<0.05). A low-calcium diet reduced and rhGH increased basal length gain and weight gain; regardless of these preconditions, daily but not bolus C increased length gain significantly. C both daily and in bolus form reduced bone osteoid content, but daily C improved mineral apposition rate more than C bolus. Total body calcium corrected for body weight decreased with a low-calcium diet, was lowest with concomitant rhGH treatment, and was not improved by C. In conclusion, daily but not bolus C treatment improves growth in uremic rats.